Enriched Satellite Cells with Pre-plate Technique Differentiate Strongly on Electrospun Polyacrylonitril Membrane - Hosseinzadeh, Simzar; Soleimani, Masoud (Regeneration, Reconstruction & Restoration (Triple R), 2017)
Introduction: Satellite cells known as the main regenerating cell types in skeletal muscle which can be isolated using pre-plate technique due to weak or slow adhesive interactions with satellite cells. Although, there are some issues about digestion of muscle tissue and isolation of satellite cells, which highlight need for an efficient procedure. Also, the employment of a nanofibrous surface can facilitate the attachment of satellite cells to reach matured muscle tissue. On the other hand, polyacrylonitrile (PAN) has been reported as a biocompatible polymer that can be electrospun into a nonwoven membrane. Materials and Methods: Herein, a modified digestion and pre-plate protocol was established for the enrichment of satellite cells. Also, a PAN electrospun scaffold was used to provide a higher surface area for cell attachment compared to tissue culture polystyrene (TCPS). However, the surface of prepared scaffold was modified with plasma treatment to progress cell adhesion. Results: The corresponding scaffold was examined with scanning electron microscopy (SEM) and tensile examination. The enriched cells, which exhibited a close gene expression pattern with satellite cells, seeded on this electrospun PAN membrane. The cultured satellite cells showed a good tendency to surface of PAN scaffold and also a higher rate of cell proliferation. Subsequently, the cells were induced to more expression of specific muscle genes compared to TCPS group. Conclusion: As a whole, satellite cells could mature to multinuclear cells using PAN scaffold as a function of efficient mechanical property and also higher surface area.